The Effectiveness of Digital Stotytelling in Teaching Speaking for Students with Different Gender Classification - Khotimah, Laily Mar'atul; Ningrum, Ary Setya Budhi; Khotimah, Khotimah (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to find out the effectiveness of using digital storytelling towards students’ speaking ability based on gender classification. The samples of this study were two classes of class IX students from MTsN 1 Kediri. The experimental group was Class IX-G, and the control group was Class IX-I. Both pretest and posttest set were used as the research instrument. To determine the effectiveness of the media utilized, ANCOVA analysis was used, and an independent sample T-test was used to determine gender differences. The study's findings revealed the effectiveness of digital storytelling to teach speaking as evidenced by sig.=.0000<.05. Further analysis proceeded to the effectiveness of digital story telling based on gender classification. As evidenced by sig. =.003.05., digital story telling was effective in teaching speaking to female students. Meanwhile, male students were not empowered. By sig=.416 >.05., there was no statistically significant difference between male students taught using digital storytelling and those taught using printed text evidence. It means that both teaching media are equally effective for teaching speaking to male students.